2014
DOI: 10.4236/ojvm.2014.45009
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Development in Foals from Four Different Breeds between Birth and Weaning

Abstract: Several studies have shown a major development in height and cannon bone circumference in foals from birth to weaning and from different breeds. However, in Brazil, there is little information about foal development. For this reason, this study has used data on foals from seven different farms in Pernambuco, Northeast Brazil, where horses have a major economic importance. The aim of this study was to compare foal's development from four breeds and to develop a regression formula in order to estimate such devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The foals were not subjected to concentrate supplementation during lactation, and weaning started at a mean body weight of 160.79 kg in CG and 153.40 kg in WG, which is slightly below the 171.55 kg and 173.5 kg cited by Rezende, Sampaio, Legorreta and Moreira (2000) and Silva Moura et al (2016), respectively, and above the 127.26 kg cited by Manso et al (2014) for foals of the Mangalarga Marchador breed.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The foals were not subjected to concentrate supplementation during lactation, and weaning started at a mean body weight of 160.79 kg in CG and 153.40 kg in WG, which is slightly below the 171.55 kg and 173.5 kg cited by Rezende, Sampaio, Legorreta and Moreira (2000) and Silva Moura et al (2016), respectively, and above the 127.26 kg cited by Manso et al (2014) for foals of the Mangalarga Marchador breed.…”
Section: Resultsmentioning
confidence: 96%
“…The values of the studied variables were found to be regular and homogeneous using the Shapiro-Wilk test. Thus, they were subjected to analysis of variance (ANOVA) for repeated measures using R software (Manso et al, 2014). The means were compared using Tukey's test at a 5% significance level (P <0.05).…”
Section: Figurementioning
confidence: 99%
“…There was a significant growth of animals within the experimental period. As reported, several factors can influence the development of foals, such as breed, age, sex, nutritional level, and so on [ 54 ]. In general, horses have a similar growth pattern in the period from 0 to 18 months of age, regardless of the breed and environmental conditions [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Authors [10] assessed the development of Quarter horse foals. And others [15] studied the development of four different breeds under tropical conditions and demonstrated that the Quarter horses had a WH and CP of ~ 91 cm and ~ 85 cm, respectively, at birth, and ~ 117 cm and ~ 122 cm, respectively, at five months of age. Upon comparison of our data with those previously reported [15], it was notable that the biometric parameters were slightly lower at birth, but similar at five months of age.…”
Section: Discussionmentioning
confidence: 99%
“…And others [15] studied the development of four different breeds under tropical conditions and demonstrated that the Quarter horses had a WH and CP of ~ 91 cm and ~ 85 cm, respectively, at birth, and ~ 117 cm and ~ 122 cm, respectively, at five months of age. Upon comparison of our data with those previously reported [15], it was notable that the biometric parameters were slightly lower at birth, but similar at five months of age. These data indicate that the supplementation did not affect the development of the animals based on comparisons with the control group and with animals reared in similar conditions.…”
Section: Discussionmentioning
confidence: 99%